A parsimonious scoring and normative calculator for the Parkinson's disease mild cognitive impairment battery. Issue 6 (3rd October 2017) - Bezdicek, Ondrej; Sulc, Zdenek; Nikolai, Tomas; Stepankova, Hana; Kopecek, Miloslav; Jech, Robert; Růžička, Evžen
Abstract: Objective : The aim of the present study was to provide a regression-based calculator that takes premorbid functioning into account to detect subtle cognitive decline, as is often present in pre-dementia states, especially mild cognitive impairment in Parkinson's disease (PD-MCI). Method : We used demographic adjustments based on sex, age, and education of 699 normative participants that fulfilled exclusion criteria for ascertaining the diagnostic accuracy of the Movement Disorders Society PD-MCI battery at Level II. We examined the clinical validity of the battery on 36 PD patients. Results : An estimated z -score was calculated for any raw score based on different models that adjust for the demographic predictors of gender, age, and education, either concurrently, individually or without covariates. We provide a useful online z -score, SD, and percentile calculator that yields estimates of cognitive impairment based on normative sample for each of the ten neuropsychological tests and enables actuarial decision-making regarding its level and profile (number of domains impaired). We document the clinical utility and applicability of the calculator on a patient with PD-MCI and show the discriminative validity of all measures in the battery by comparing PD-MCI and PD without cognitive impairment with the highest area under the curve (.94) for Tower of London at −2 SD threshold. Conclusions : Our normative calculator introduces a practical web-based psychometric tool for the evaluation of PD-MCI status in clinical settings. We show the detection potential of each of ten measures included in the battery and delineate the diagnostic precision of the PD-MCI battery.